2013
DOI: 10.1021/ie300841m
|View full text |Cite
|
Sign up to set email alerts
|

Solid Oxide Fuel Cell System Utilizing Syngas from Coal Gasifiers

Abstract: Integrated gasification fuel cell (IGFC) plants incorporating solid oxide fuel cells (SOFCs) are attractive alternatives to traditional pulverized coal-fired steam cycle and integrated gasification combined cycle power plants for centralized power generation. Key features of the IGFC power plants are high efficiency, near-zero emissions of SOx and NOx, low water consumption, and amenability to carbon dioxide (greenhouse gas) capture. Recent SOFC technology advancements and increased power density are indicativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…For this, syngas (H 2 + CO) produced from biomass, waste, or natural gas is transformed into synthetic diesel fuel and gasoline by means of the Fischer− Tropsch (FT) process. 2 Syngas can also be employed for electricity generation in solid oxide fuel cells, 3 methanol production, 4 and dimethyl ether synthesis. 5 Steam reforming of methane (SRM, Scheme 1) is a commonly used industrial process to produce syngas.…”
Section: Introductionmentioning
confidence: 99%
“…For this, syngas (H 2 + CO) produced from biomass, waste, or natural gas is transformed into synthetic diesel fuel and gasoline by means of the Fischer− Tropsch (FT) process. 2 Syngas can also be employed for electricity generation in solid oxide fuel cells, 3 methanol production, 4 and dimethyl ether synthesis. 5 Steam reforming of methane (SRM, Scheme 1) is a commonly used industrial process to produce syngas.…”
Section: Introductionmentioning
confidence: 99%
“…Various fuels can be used in SOFCs for power generation, including H2, CO, methane, syngas and other kinds of carbon-based fuel. Several groups have shown that SOFCs can operate directly on hydrocarbon fuels, including higher hydrocarbons (Kee, R J 2004, Ghezel-Ayagh H 2013 Well known SOFC suppliers including Fuel cell Energy, Bloom Energy, GE , MHI, etc. Among that the most commercially successful SOFC company should be Bloom Energy, whom sold 687 , 622 sets of 100KW SOFC system in 2016 and 2017, their SOFC systems have been installed and applied in numerous famous companies such as Apple, Coca-Cola and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline materials such as CaO have high sorption capacities and rapid kinetics, making them suitable candidates for CO 2 capture [2][3][4]. High temperature CO 2 capture by CaO has been studied in related works [5][6][7]; they demonstrate that warm CO 2 capture with calcium oxides is feasible for use in related industrial applications.…”
Section: Introductionmentioning
confidence: 99%